Jorge L. Garcia Venturini, Filosofía de la Historia, Biblioteca Hispánica de Filosofía, Editorial Gredos, Madrid, 1972, 266 pp. - Lértora Mendoza, Celina A. (1974)
Fil: Lértora Mendoza, Celina A. Investigador independiente